Development and content validity of the DizzyQuest - Martin, E. C.; de Joode, L. E. G. H.; Lucieer, F.; Sitters, D.; Delespaul, P. A. E. G.; Leue, C.; van de Weijer, S. C. F.; Meijers-Erdkamp, A.; Grill, E.; Zwergal, A.; Guinand, N.; Perez-Fornos, A.; et al. (Frontiers in Audiology and Otology, 2024)
Introduction Vestibular disorders have a high prevalence and impact on general health. Currently questionnaires to measure vestibular symptoms and the impact on daily life, do not capture disease-specific symptoms or induce recall bias. The DizzyQuest was introduced, to measure vestibular symptoms in the flow of daily life, using the ecological momentary assessment (EMA) strategy. The development and content validity of the DizzyQuest are described in this article. Methods The development process consisted of two stages: First, the development of a concept version of the DizzyQuest based on the conceptual model of positive health, semi-structured interviews with patients diagnosed with bilateral vestibulopathy (BV) and expert input. Second, the assessment of content validity through a 4-week pilot trial, followed by focus group meetings with patients and professionals separately. Results Patient interviews, an expert meeting and a conceptual model resulted in the first pilot version of the DizzyQuest, which included a morning-, within-day-, evening- and attack-questionnaire. To report patient characteristics, complimentary patient- and doctor-questionnaires were added. The pilot trial (N = 5) and two patient focus group meetings resulted in multiple suggestions for response options. Two professional focus group meetings provided recommendations for sampling time and sampling schedule. As a result, two versions of the DizzyQuest were developed, consisting of a regular DizzyQuest (DQ) and an extended DizzyQuest-XL (DQ-XL). Conclusion The DizzyQuest enables the administration of multiple questionnaires during the flow of daily life, therefore increasing reliability and ecological validity. The DQ and DQ-XL, using a big data approach, has the potential to improve precision medicine.